Characterisation of surface organisation and morphology of some new experimental dental resin-based composites. (19th March 2012) - Prejmerean, Cristina; Tomoaia-Cotisel, Maria; Vasile, Eugeniu; Furtos, Gabriel; Pop, Lacramioara; Moldovan, Marioara; Sarosi, Codruta; Petean, Ioan
The aim of this work was to investigate the morphology and to determine the roughness of a series of three new experimental resin-based composite materials containing different inorganic fillers using the AFM technique. Dental composites with photochemical initiation of polymerisation were prepared using the same resin consisting of synthesised aromatic dimethacrylic oligomers mixture containing Bis-GMA monomer – 2, 2-bis[4-(2-hydroxy-3-methacryloyloxypropoxy) phenyl]-propane and the corresponding Bis-GMA dimer and triethyleneglicol dimethacrylate. The inorganic fillers used in the composites were: From the point of view of the surface uniformity, we can conclude that the smoothest surface results from the composite based on synthesised hydroxyapatite, followed by the composite based on commercial hydroxyapatite, the highest roughness being observed for the composite based on glass filler particles. All three composite materials present compact structures of undermicronic particles uniformly assembled.